Segovia at Los Olivos - Nupen, Christopher; Nupen, Christopher
A film of the great guitarist Andrés Segovia, at home at Los Olivos in Andalucia in July, 1967. Segovia looks back on his long career, discusses the gradual acceptance of the guitar and the music he has inspired composers to write. The film includes performances by Segovia of music closely associated with him and includes scenes at the Alhambra in Granada, to the background of the master's playing of Tarrega's Recuerdos de la Alhambra
Title from resource description page (viewed Jul. 25, 2014)
Keywords: Guitar music; Segovia, Andrés / 1893-1987; Documentary films; Streaming videos